MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) - Nurhazannah, Yunie (Jurnal Pendidikan Matematika dan IPA, 2017)
This study aims to determine the improvement of student learning outcomes in the system of linear equations of two variables using Student Team Achievement Division (STAD) type cooperative learning model in class VIII E SMPN 21 Pontianak academic year 2016/2017. Data collection was obtained by direct observation and test. Subjects are students of class VIII SMPN 21 Pontianak with 38 students of students consisting of 16 male students and 22 female students. This classroom action research consists of two cycles. Each cycle stage consists of planning, implementation, observation and reflection. The results of data analysis that replicate the first half of the academic year 2015/2016 shows that students who learn completeness of students has just reached 10.58%. His performance is low. The instruments used in this classroom action research are: (1) Student Activity Observation Sheet; (2) Observation Sheet of teacher teachers in learning activities; (3) Written test (Test Cycle I and Cycle II). Results of learning data from the first cycle to cycle II obtained more than 75% of students who graduated. This study revealed that the use of cooperative learning model STAD can improve student learning outcomes on linear equations system in two variables E class VIII SMP Negeri 21 Pontianak.Keywords: learning outcomes, Student Team Achievement Division (STAD), Systems of Linear Equations in Two Variables (SPLDV)